In-situ synthesis of high-entropy Al2O3/RE3Al5O12/ZrO2 ceramic by laser powder bed fusion with exceptional properties - Zhiwei Xiong; Kai Zhang; Wenhe Liao; Tingting Liu; Yang Zhang; Zhiguang Zhu (Journal of Advanced Ceramics)
Eutectic ceramics with exceptional hardness, elevated Young’s modulus, and impressive fracture toughness have become indispensable materials for various demanding industrial applications in extreme environments. In this work, in-situ synthesis of high-entropy Al2O3/(Y0.2Eu0.2Er0.2Yb0.2Lu0.2)3Al5O12/ZrO2 ceramics was successfully achieved with one-step slurry-based laser powder bed fusion (LPBF). The phase formation, microstructure morphologies, phase distribution, crystallographic characteristics, and mechanical properties were systematically investigated. The typical microstructure of a shell–core architecture resembling cell-like features consists of both crystalline and amorphous phases. The selective aggregation of constituents is the combined outcome of solute exclusion and convective transport mechanisms. The crystallographic orientation relationships inside the shell may include [1¯10]ZrO2//[111]RE3Al5O12 and (21¯1¯)RE3Al5O12//(111¯)ZrO2. During the rapid cooling of LPBF, the amorphous phase is an intermediate metastable product of crystal structure adjustment (REAlO3, RE4Al2O9 → amorphous phase → RE3Al5O12). Owing to the slower diffusion rate and higher transition energy threshold of Eu elements, more Eu elements are retained in the amorphous phase. Structural analysis indicates that the remarkable mechanical properties can be attributed to several factors, including the significant dissociation energy, strong cationic field, and stress transfer among Al2O3, RE3Al5O12, ZrO2, and the amorphous phase. Additionally, the cocktail effect and plastic deformation mechanism of the high-entropy shell contribute to these properties.